‘Security’ and ‘Crisis’ in Populist Discourse -a brief exploratory study- - Oanca, Alexandra (Acta Universitatis Danubius. Relationes Internationales, 2022)
Prior to the COVID pandemic and the more recent conflict in Ukraine, populist parties in the European Union enjoyed a growing popularity among voters. Some of them became part of government coalitions or held executive power alone. This article aims to provide a comparison of six populist parties’ narratives on security, based on content analysis of official English-language party documents. Quantitative findings indicate some clear differences between left and right-wing populist parties in terms of references to key words “security” and “crisis”. A qualitative exploration of collocations further suggests which security sectors - societal, military, political, economic, or environmental - these parties tend to prioritize.